L’éducation des adultes dans les universités en France. Une mission hétérodoxe ? - Christelle Manifet (Cahiers de la Recherche sur l'Education et les Savoirs)
Lifelong training includes a variety of educational experiences, from the initial traditional college years to the resumption of studies in adulthood through short or long courses, taken part-time or full-time, and with the objective to graduate with a vocational degree or for personal cultural interest. In a comparative perspective and considering the convenient indicator of the students’ age average, French universities don’t really fulfill these expectations and needs. Although, evaluating this contribution can only be correctly done by considering the historical conditions in which the problem of adult education has been called into question in French society and its public sphere, independently from the skills, categories of perception and response of the academic policy. Thus, adult education is a heterodox activity in universities, structured by the statutory references of the labor and employment policies and driven by a social democrat philosophy of State intervention, but integrated in a higher education sector to which autonomy of the education system and centrality of the State’s action are dominant institutional features. In this paper, the analytical challenge consists in producing a History of French adult education at university level, by focusing on its inherited structures without underestimating the social and institutional dynamics that foster changes. Various phenomena such as shifts, hybridization and contradictions suggest the exhaustion of this institutional model.